Pengaruh Range of Motion (ROM) Aktif Kaki terhadap Sensitivitas Kaki pada Pasien Diabetes Millitus Tipe II di Wilayah Kerja Puskesmas Masbagik - Dewi Purnamawati; Yulia Tri Kresnawati; Ely Mawaddah; Aan Dwi Sentana (Bima Nursing Journal, 2022)
In the era of globalization there is a shift from infectious diseases to non-communicable diseases, more and more degenerative diseases, one of which is Diabetes Millitus. DM is a metabolic disease characterized by increased blood sugar levels due to insulin secretion disorders. Hyperglycemia and metabolic disorders in DM can cause complications, one of which often occurs in DM patient is nerve damage or peripheral neuropathy so that it can cause a decrease in foot sensitivity. The purpose of this study was to determine the influence of foot active range of motion (ROM) on the sensitivity of foot in patients Diabetes Millitus type II in the working area of primary health care  Masbagik year 2021. This study is a pre-exsperimental research design with One Grup Pretest-Posttest. Approach. The sample in this study is patients with Diabetes Millitus type II in the working area of primary health care Masbagik 22 people sampel. Sampling technique using Purposive sampling. Statistical test results show that there is an effect of active foot Range Of Motion (ROM) on foot sensitivity in patients Diabetes Millitus type II with P test results, namely p value = 0.000 < a = 0.05, where the null hypothesis (H0) is rejected or the alternative hypothesis (Ha) accepted, It can be concluded that there is an effect of foot active range of motion (ROM) on the sensitivity of foot in patients Diabetes Millitus type II. Respondents are advised to always do Range Of Motion (ROM) active foot of the foot to maintain foot sensitivity. If foot sensitivity is not maintained, the roots experience impaired foot sensitivity which can cause diabetic ulcers or diabetic foot.